Root cause analysis of the fracture of a sonar window caused by hydrostatic, hydrodynamic, and transient forces around a ship. (February 2015) - Han, Hyung-Suk; Lee, Kyung-Hyun
Highlights: RCA of the fracture of a sonar window of a typical naval vessel was performed according to VDI 3822. Buckling of the sonar window can occur when flooding valve of WMS is closed under rough sea condition. The root cause of the sonar window fracture is studied using FEM and test of the real ship. Abstract: Sonar systems are installed in naval vessels to inspect objects in the sea. When the system is installed at the bulbous bow of the ship, it can be vulnerable to fractures in rough seas due to hydrostatic and hydrodynamic forces, such as fluid-induced forces, and transient forces, such as slamming and collision with submerged foreign objects. In this paper, root causes analysis (RCA) of the fracture of a sonar window of a typical naval vessel was performed. To identify the root causes of the fracture, a numerical analysis was performed of the stress distribution on a sonar window under various extreme conditions. The results of the analysis, together with hypotheses of the causes of the fracture, are presented. The results of the analysis were verified by measuring the stress on the sonar window under typical sailing conditions of ships. The RCA demonstrated that buckling in response to the hydrostatic forces applied under the typical operating conditions of a water management system (WMS), in addition to excessive slamming, can cause a sonar window to fracture. Based on this RCA, corrective actions to prevent sonar window fractures include changing the material of the window and the operating conditions of the WMS.